Endoscopic methods in the management of hepatic hydatid disease complications - Uğur YILMAZ; Burhan ŞAHİN and Sedat BOYACIOĞLU and Ülkü SARITAŞ and Çağlar BAYSAL and Musa AKOĞLU (Turkish Journal of Gastroenterology, 2020)
-